Natural Geographic Time: Toward a New Conceptual Framework for Understanding the Spatial and Temporal Dynamics of Time on Earth (Al-Farooq Journal of Sciences, 2026)
This study aimed to investigate the spatial and seasonal behavior of plastic debris in the investigated coastal environment by assessing its abundance, composition, probable sources, transport pathways, and the combined influence of anthropogenic and marine-seasonal factors on its accumulation and redistribution. A descriptive-analytical field approach was adopted, based on repeated monitoring during winter, spring, summer, and autumn using standardized coastal surveys and systematic transects. Plastic debris was evaluated in terms of item abundance, weight, size distribution, probable source, and associated environmental conditions.The findings revealed pronounced spatial and seasonal variability in plastic pollution, with recorded quantities ranging from 5.09 to 24.36 g. Naeama recorded the highest summer value (24.36 g), whereas Al-Haniya reached its maximum during winter (14.09 g), and Bahar Sharika peaked in spring (17.35 g), demonstrating the absence of a single seasonal accumulation pattern across all sites. Detailed size-class data further showed that smaller particles were generally more abundant numerically, whereas larger debris contributed more substantially to total mass.The results indicate that plastic-debris dynamics are governed by interactions among land-based and marine-based inputs, site characteristics, human pressure, winds, waves, and coastal currents. Consequently, high-density locations should not automatically be interpreted as direct pollution sources, since some may function primarily as receiving or retention zones for transported debris. The study concludes that effective plastic-pollution management requires repeated spatial and seasonal monitoring, hotspot identification, and site-specific interventions rather than uniform coastal management measures. It recommends establishing a sustainable coastal monitoring program, improving waste-management practices, reducing single-use plastics, and integrating debris observations with marine and climatic data through GIS-based monitoring systems to support evidence-based coastal management.
Keywords: Plastic debris; Coastal pollution; Seasonal variation; Spatial distribution; Pollution hotspots; Marine litter; Libya